Editorial - Prestrelo, Eleonôra Torres; Soares, Adriana Benevides; Feijoo, Ana Maria Lopes Calvo; Uziel, Anna Paula; Ewald, Ariane Patrícia; Mancebo, Deise (Estudos e Pesquisas em Psicologia, 2009)
Eleonôra Torres Prestrelo, Adriana Benevides Soares, Ana Maria Lopes Calvo Feijoo, Anna Paula Uziel, Ariane Patrícia Ewald, Deise Mancebo